FEM Analysis of Squirrel Cage Induction Motor Fed with Raised Sine Wave Supply - Balakrishnan M S; Theagarajan R (Institute of Advanced Engineering and Science, 2013)
AC motors are used frequently for many industrial applications such as material handling, traction, electric vehicles etc. A novel non-sinusoidal modulation technique employing Raised Sine Wave (RSW) for the PWM inverter is proposed in this paper. Squared Sine Wave has a distinct advantage of reduced rate of change at zero crossing of each half cycle, and eliminates the need for dead band. An Finite Element Analysis (FEM) is carried out to study its suitability for AC Induction Motor. The results show that the operation has a constant startup torque for all load conditions, thus providing a smooth start from zero speed to full rated speed. This feature makes it most suitable for applications requiring frequent startup such as traction. The operation of the conventional Variable Frequency Drives using Conventional Sine Wave (CSW) is compared with the results obtained with RSW supply.DOI:http://dx.doi.org/10.11591/ijece.v3i2.1705